2017
DOI: 10.1212/wnl.0000000000003889
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal hypometabolism in older adults with memory complaints and increased amyloid burden

Abstract: Objective: To identify the functional and pathologic correlates underlying subjective memory complaints (SMCs) in cognitively normal older adults.Methods: Two hundred fifty-one older adults underwent resting-state fluorodeoxyglucose (FDG)-PET and Pittsburg compound B-PET b-amyloid (Ab) imaging and filled out a questionnaire regarding SMCs. Participants were classified into 2 groups based on their Ab burden. Age-adjusted voxel-wise correlations were used to examine SMCs, amyloid status (Ab 1 vs Ab 2 ), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 36 publications
2
49
0
Order By: Relevance
“…According to the pathophysiological viewpoint presented in this paper, connectivity between brain regions, within and between the ON and DMN, might be aberrant to a greater extent in MCI converters. For instance, there is evidence for impaired FC in AD between the posterior cingulate cortex (PCC) and the hippocampus, probably as a consequence of early structural alterations in the hippocampal formation (Schultz et al., ; Vannini et al., ). The hippocampus, while not part of the core ON, is nonetheless involved in olfactory processing (Gottfried, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the pathophysiological viewpoint presented in this paper, connectivity between brain regions, within and between the ON and DMN, might be aberrant to a greater extent in MCI converters. For instance, there is evidence for impaired FC in AD between the posterior cingulate cortex (PCC) and the hippocampus, probably as a consequence of early structural alterations in the hippocampal formation (Schultz et al., ; Vannini et al., ). The hippocampus, while not part of the core ON, is nonetheless involved in olfactory processing (Gottfried, ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with SMI are defined as those with subjective reports of memory function decline whilst the objective neuropsychological assessments are within the normal range. Substantial evidence has shown that SMI may increase the risk of AD and MCI . SMI may serve as a pre‐MCI condition .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, early detection of biomarkers and the biological basis of SMI attract growing attention from researchers. Numerous studies have demonstrated that individuals with SMI tend to present abnormal imaging biomarkers similar to AD and aMCI , especially in the hippocampus and entorhinal cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SCD at baseline also showed progressive neuronal degeneration, which was associated with the degree of further cognitive decline (Stewart et al, ). From the view point of biomarkers studies, SCD has been shown to be associated with hypometabolism in AD‐related brain regions using brain positron emission tomography, and a higher prevalence of brain amyloid deposition has been observed among SCD patients than in normal subjects without memory complaints (Amariglio et al, ; Vannini et al, ). In addition, an abnormal CSF biomarker was found to be well correlated with the risk of SCD transitioning to AD dementia (Sierra‐Rio et al, ; Wolfsgruber et al, ).…”
Section: Introductionmentioning
confidence: 99%